Analysis of Bolted Joints 2003
DOI: 10.1115/pvp2003-1881
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Thermal and Mechanical Behaviors of Bolted Joint

Abstract: Mechanical and thermal behaviors of the bolted joint subjected to thermal load are analyzed using axisymmetric FEM, where the effects of thermal contact resistance at the interface and heat flow through small gaps are taken into account in order to accurately evaluate the variations of bolt preloads. It is expected that the numerical procedure proposed here provides an effective means for estimating the strength of such critical structures as internal combustion engines, pressure vessels, steam and gas turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Thus, the calculation of effective conductance in this area is simplified based on the experimentally obtained function. 24 Heat transfer away from the MP is dominated by the Fourier heat conduction equation, which could be expressed as follow:…”
Section: Thermal Contact Condition At Substrate Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the calculation of effective conductance in this area is simplified based on the experimentally obtained function. 24 Heat transfer away from the MP is dominated by the Fourier heat conduction equation, which could be expressed as follow:…”
Section: Thermal Contact Condition At Substrate Interfacementioning
confidence: 99%
“…However, it is usually simplified in above models without physical explanation, which has been proved non-negligible in some situations. In the analysis of thermal and mechanical behavior of bolted joint, Fukuoka et al 24 studied the effect of thermal contact resistance at the interface, and they concluded that it is non-negligible on the calculation of thermal stress. Li et al 25 developed a FEM model and numerically investigated the effect of thermal contact in thermal resistance welding and results showed that the formation of weld nugget was largely affected by the surface roughness of the electrodes when its value exceeded a threshold.…”
Section: Introductionmentioning
confidence: 99%